A Study on the Current Status of Psychological Counseling Services for High School Students in an Giang Province, Vietnam - Nguyen Bach Thang (Fakultas Tarbiyah Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
Based on surveys, field observations, and an analysis of the current situation, the author identified fundamental factors affecting psychological counseling activities for high school students in An Giang Province, Vietnam. This serves as a basis for school principals in An Giang Province to develop and implement solutions to improve the quality of psychological counseling services for students. This effort contributes to building a friendly school environment, fostering active students, developing comprehensive learning and life skills, and nurturing well-rounded personalities. It creates a healthy pedagogical environment where students can showcase their positive qualities in their academic pursuits.